Monetary policy shocks and peer-to-peer lending in China - Michael Funke; Xiang Li; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
This paper studies monetary policy transmission in China's peer-to-peer lending market. Using spectral measures of causality, we explore the impacts of Chinese monetary policy shocks on China's P2P market interest rates and lending amounts. The estimation results indicate significant spectral Granger causality from monetary policy surprises to P2P lending rates for borrowers, but not the reverse. Unlike the lending channel for traditional banks, monetary policy shocks do not Granger-cause the credit amount in the P2P lending market.
URN:NBN:fi:bof-201912091699
Keywords: E52; E43; G23; C22; 330